DETERMINAN STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI TAHUN 2019 - 2022 - Febri, Yossyca Febri Damayanti; Suhendro; Endang Masitoh (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
ABSTRAC This investigation aims to identifity the most crucual components influencing capital structure of manufacturing companies within the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. This investigation considers asset structure, liquidity, and sales growth. Out of 80 companies in the sample, 69 meeting the criteria were selected for the quantitative study. Multiple linear analysis was utilizwd to assess the impact of idependent variables on the dependent variable. The results indicate that asset structure and liquidity significantly influence the capital structure, while sales growth does not have a significant impact.